Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1111/j.1746-1561.2006.00119.x
|View full text |Cite
|
Sign up to set email alerts
|

The Breathmobile™: A Novel Comprehensive School-Based Mobile Asthma Care Clinic for Urban Underprivileged Children

Abstract: Urban minority children have higher rates of asthma morbidity due to multiple factors. Many school-based programs have been funded to improve asthma management, especially for these "high-risk" inner-city children with asthma. Here we report the outcomes of the Children's Hospital of Orange County Breathmobile program, which is a school-based asthma program that combines the use of a mobile clinic and a pediatric asthma specialist. Baseline evaluations included a detailed history and physical, skin prick test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 24 publications
(24 reference statements)
0
24
0
Order By: Relevance
“…32 An alternative strategy has been to provide a mobile medical van that on a regular schedule brings health care providers, examination space, and medical supplies to the school so that students may receive diagnostic and treatment services with scheduled follow-up visits. Two studies have shown that comprehensive asthma care provided through mobile vans reduced hospitalizations and ED visits, 33,34 symptoms and rescue inhaler use, 33 and school absences. 34 Another strategy involves a partnership among school staff, health care providers, and parents to identify students who need daily therapy and have shown or are at risk for poor compliance, and provide supervised daily controller therapy at the school.…”
Section: Strategies To Improve Access To Carementioning
confidence: 98%
See 1 more Smart Citation
“…32 An alternative strategy has been to provide a mobile medical van that on a regular schedule brings health care providers, examination space, and medical supplies to the school so that students may receive diagnostic and treatment services with scheduled follow-up visits. Two studies have shown that comprehensive asthma care provided through mobile vans reduced hospitalizations and ED visits, 33,34 symptoms and rescue inhaler use, 33 and school absences. 34 Another strategy involves a partnership among school staff, health care providers, and parents to identify students who need daily therapy and have shown or are at risk for poor compliance, and provide supervised daily controller therapy at the school.…”
Section: Strategies To Improve Access To Carementioning
confidence: 98%
“…Two studies have shown that comprehensive asthma care provided through mobile vans reduced hospitalizations and ED visits, 33,34 symptoms and rescue inhaler use, 33 and school absences. 34 Another strategy involves a partnership among school staff, health care providers, and parents to identify students who need daily therapy and have shown or are at risk for poor compliance, and provide supervised daily controller therapy at the school. Because adherence to asthma treatment regimens is typically below 50%, it is an important factor in morbidity.…”
Section: Strategies To Improve Access To Carementioning
confidence: 98%
“…Ongoing control, however, was not constant and varied significantly across all levels of asthma severity. Liao et al (61) showed that subsequent to receiving ongoing care in a mobile unit, participating children had significant declines in their annual rate of visits to an emergency department and/or hospitalization. School absences also declined.…”
Section: School-focused Studiesmentioning
confidence: 99%
“…On the one hand, asthma at these ages is frequently overlooked and sometimes undertreated [2,3]. Wheezy patients often become in remission, however, the lung function in children with persistent wheeze becomes reduced by age 6 in several cases [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…L-Carbocystein was also used for proper mucociliary clearance to prevent infectious processes, sinusitis and/or bronchitis [3].…”
Section: Introductionmentioning
confidence: 99%